2020
DOI: 10.1101/2020.05.15.095174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electromembrane extraction and mass spectrometry for liver organoid drug metabolism studies

Abstract: 33Liver organoids (miniature, organ-like biomaterials derived from e.g. a patient´s stem 34 cells) are emerging tools for precision drug development and toxicity screening. We 35 demonstrate that electromembrane extraction (EME) is suited for collecting organoid-36 derived drug metabolites prior to mass spectrometry (MS)-based measurements. 37 EME, which is essentially electrophoresis across an oil membrane, allowed drugs 38 and drug metabolites to be separated from medium components (albumin, etc.) that 39 co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Samples were stored at -80 °C prior to analysis. For these experiments, the determination of heroin, 6-AM, and morphine were performed using UHPLC-MS as previously described by Skottvoll et al [13].…”
Section: Heroin Stability Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were stored at -80 °C prior to analysis. For these experiments, the determination of heroin, 6-AM, and morphine were performed using UHPLC-MS as previously described by Skottvoll et al [13].…”
Section: Heroin Stability Testingmentioning
confidence: 99%
“…Verpoorte and co-workers have previously combined organs/organ models, chip microfluidics and separation science, for studying metabolism of liver slices [11] and pharmacology in a gut-on-chip [12]. We have recently coupled liver organoids with sample preparation techniques such as electromembrane extraction (EME) [13], which we also found to be compatible with on-line coupling of organoid-containing chips to LC-MS for studying organoid drug metabolism [14]. However, EME requires an electrical current driven transfer of metabolites through an oil membrane into an MS-compatible solution which can potentially limit the spectrum of analytes that can be analyzed [14].…”
mentioning
confidence: 99%
“…These biomaterials/microphysiological systems, which may be grown from, for example, induced pluripotent stem (iPS) cells or patient cells, are emerging as powerful tools for, for example, drug discovery and development biology, serving as alternatives to animal models and conventional cell cultures [2]. Recently, we have studied drug metabolism traits of liver organoids, using 96‐well electromembrane extraction (EME) [3] and on‐chip EME [4]. In the latter study, we coupled the on‐chip format directly with mass spectrometry, allowing a high degree of automation and specificity, leading us to conclude that organoids/chip systems and mass spectrometry is a well‐suited pairing.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectrometry has been utilized in biotransformation studies for more than 50 years and with the introduction of liquid chromatography into the system, LC-MS has become the standard analytical tool for the analysis of samples from metabolism studies (Wen and Zhu, 2015) and there is continuous development directed towards improving the sensitivity and efficiency in detecting metabolites as well as facilitating structural identification. Cyclic ion mobility (cIM) mass spectrometry applied to the resolution of isomeric acylglucuronides, (Higton et al, 2021), and on-line coupling of electromembrane extraction with MS to study drug metabolism in liver spheroids (Skottvoll et al, 2021) are two examples of advances recently reported in this area. It is important to remember that LC-MS can also be further coupled with NMR to enable unambiguous characterization of metabolites in an efficient manner.…”
mentioning
confidence: 99%